LABOUR MARKET TRENDS AND THEIR IMPACT ON HUMAN RESOURCE MANAGEMENT IN LITHUANIAN COMPANIES - Česynienė, Rima; Diskienė, Danutė; Stankevičienė, Asta (Ekonomika, 2013)
Abstract. During the last decades, organizations operate in changing labour market conditions. Labour markets of many countries, including Lithuania, are in a continuous state of changes which demand a new approach to the management of human resources. The purpose of this study was to identify the key factors that transform labour markets and to outline how this transformation is impacting human resource management practices, particularly human resource specialists’ functions and competences. To achieve this purpose, a detailed review of literature was performed and a research based on the questionnaire method was conducted in 2011–2012 in 92 Lithuanian companies. The research included 160 respondents – specialists of human resourcesdepartments. The research has demonstrated that, in the changing labour market conditions, the functions of human resource specialists have become more diverse and are increasingly directed towards fulfilling the needs of the business.Key words: labour market, human resource management, functions, competences